TEACHER AS A FACILITATOR OR A TEACHER: EMPOWERING LEARNING STRATEGIES IN GEOMETRY COURSE - Wanda Nugroho Yanuarto (Universitas Islam Malang, 2015)
Teaching is the well known word for teachers. Teachers know the meaning of this word and know how to perform teaching. Sometimes they do not know the difference between teaching and facilitating in learning and it make a distance between the students and teachers. The purpose of this study are how learning geometry in mathematics education, Teacher Training and Education Faculty at the University of Muhammadiyah Purwokerto, Indonesia modify the class in geometry course interactively and can be easily understood by students. So, the researchers made the strategies in geometry course that is associated with the games. Games are one of strategy in class which is support for the student to understand the geometry with easily and make the class interactively.